Board Gender Diversity and Financial Performance: A Bibliometric Perspective in the Context of Emerging Markets: Board Gender Diversity and Financial Performance: A Bibliometric Perspective in the Context of Emerging Markets - Tri Lestari (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
This study aims to provide a bibliometric overview of research on board gender diversity and financial performance published between 2020 and 2026. Using the Scopus database, 158 peer-reviewed articles were identified through a structured search strategy and analyzed using bibliometric techniques, including performance analysis and keyword co-occurrence mapping. The findings reveal a significant increase in publication output, particularly after 2022, indicating growing academic attention toward gender diversity within corporate governance research. The intellectual structure of the field is primarily anchored in the governance–performance nexus, with board gender diversity, corporate governance, and financial performance emerging as dominant themes. Recent studies increasingly integrate sustainability, ESG performance, and corporate social responsibility, reflecting the evolving complexity of the diversity–performance relationship. The results also show geographic concentration of research output in selected countries, suggesting opportunities for broader contextual exploration. This study contributes by systematically mapping the development, thematic clusters, and influential works in this domain, and by providing recommendations for future research.